2006
DOI: 10.1177/00238309060490030201
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Speech Events in Two Speech Databases of Human-Computer and Human-Human Dialogs in Spanish

Abstract: Previous works in English have revealed that disfluencies follow regular patterns and that incorporating them into the language model of a speech recognizer leads to lower perplexities and sometimes to a better performance. Although work on disfluency modeling has been applied outside the English community (e.g., in Japanese), as far as we know there is no specific work dealing with disfluencies in Spanish. In this paper, we follow a data driven approach in exploring the potential benefit of modeling disfluenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There were also more cut-offs in the L2 narrations, although, the difference in the rate of cut-offs was not statistically different between the two languages. A comparison of the various types of disfluencies falls outside the scope of this study but previous work (Lopez-Ozieblo 2017;Machuca, Llisterri and Ríos Carratalá 2015;Rodríguez and Torres 2006) has identified a tendency for filled pauses and elongations, in addition to cut-offs, in Spanish L1 speakers. On the other hand, Lecumberri, Cooke and Wester (2017) observed similar patterns in the cut-offs of English and Spanish native speakers.…”
Section: Cut-off Ratesmentioning
confidence: 95%
“…There were also more cut-offs in the L2 narrations, although, the difference in the rate of cut-offs was not statistically different between the two languages. A comparison of the various types of disfluencies falls outside the scope of this study but previous work (Lopez-Ozieblo 2017;Machuca, Llisterri and Ríos Carratalá 2015;Rodríguez and Torres 2006) has identified a tendency for filled pauses and elongations, in addition to cut-offs, in Spanish L1 speakers. On the other hand, Lecumberri, Cooke and Wester (2017) observed similar patterns in the cut-offs of English and Spanish native speakers.…”
Section: Cut-off Ratesmentioning
confidence: 95%
“…A study of speech recognition in Spanish confirmed the frequency and acoustic predictability of fillers, and demonstrated that incorporation of such utterances as lexical items (rather than noise) in models of automatic speech recognition improves the recognizer's performance (Rodriguez & Torres, 2006).…”
mentioning
confidence: 93%
“…20,21 Findings of these studies include an overall disfluency rate of 4 to 6 disfluencies per 100 words in Spanish, which is similar to reports of disfluency rates reported in adult-directed speech in English. 9,17 The common Spanish filled pauses ah, eh, and mm were found to occur at a rate of 1.67 per 100 words. In another corpus set of mostly formal language monologues, speakers produced an average of 5 disfluencies per 100 words (not including silent pauses); around 1.5 per 100 words were fillers.…”
Section: Typical Disfluencies In Monolingual English and Monolingual mentioning
confidence: 99%
“…10 In short, typical disfluencies are common in English spontaneous speech, and this finding has been replicated in other languages, including Chinese, Croatian, Dutch, German, Norwegian, Japanese, Russian, Spanish, Swedish, and Tok Pisin, suggesting the universality of these types of disfluencies in language production. [11][12][13][14][15][16][17][18][19] Several corpora-based studies have informed our knowledge of disfluencies in spontaneous speech dialogues in Spanish. In general, these studies report similar types of disfluencies as those reported for monolingual English speakers, including retracings, filled pauses, and hesitations/silent pauses.…”
Section: Typical Disfluencies In Monolingual English and Monolingual mentioning
confidence: 99%